Characterising lower-body musculoskeletal morphology and whole-body composition of elite female and male Australian Football players - Callum J. McCaskie; Marc Sim; Robert U. Newton; Jarryd Heasman; Brent Rogalski; Nicolas H. Hart (BMC, 2022)
Abstract Background Physical demands and injury rates differ between elite female and male Australian Football (AF) players. To improve understanding of contributing physical factors to these differences, the purpose of this study was to investigate lower-body morphology and whole-body composition of elite footballers competing in the Australian Football League (AFL) and Australian Football League Women's (AFLW). Methods Lower-body morphology and whole-body composition of 23 AFL players and 23 AFLW players were assessed using peripheral Quantitative Computed Tomography and Dual-energy X-ray Absorptiometry at the beginning of pre-season. Differences between cohorts, with sub-analyses of kicking vs. support limbs, and experienced vs. inexperienced player status were assessed using two-sample independent t-tests. Magnitude of differences were assessed using Cohen's d effect sizes. Results AFL players had greater absolute (p < 0.001; ES = 3.28) and relative (p < 0.001; ES = 2.29) whole body lean soft-tissue mass, with less absolute (p = 0.004; ES = 0.91) and relative (p < 0.001; ES = 2.29) fat mass than AFLW players. For AFLW players, no significant differences existed between kicking and support limbs with few differences observed between experienced and inexperienced players. Conclusions Greater emphasis on physical development in AFLW players may be required to enable increases in muscle mass and skeletal robustness, to ensure they can tolerate the loads of elite competition.